A systematic review of the relationship between objective measurements of the urban environment and psychological distress. (November 2016) - Gong, Yi; Palmer, Stephen; Gallacher, John; Marsden, Terry; Fone, David
Abstract: The urban environment has become the main place that people live and work. As a result it can have profound impacts on our health. While much of the literature has focused on physical health, less attention has been paid to the possible psychological impacts of the urban environment. In order to understand the potential relevance and importance of the urban environment to population mental health, we carried out a systematic review to examine the associations between objective measurements of the urban environment and psychological distress, independently of the individual's subjective perceptions of the urban environment. 11 peer-reviewed papers published in English between January 2000 and February 2012 were identified. All studies were cross-sectional. Despite heterogeneity in study design, the overall findings suggested that the urban environment has measurable associations with psychological distress, including housing with deck access, neighbourhood quality, the amount of green space, land-use mix, industry activity and traffic volume. The evidence supports the need for development of interventions to improve mental health through changing the urban environment. We also conclude that new methods for measuring the urban environment objectively are needed which are meaningful to planners. In particular, future work should look at the spatial-temporal dynamic of the urban environment measured in Geographical Information System (GIS) in relation to psychological distress. Highlights: A systematic review examines the associations between objective measurements of the urban environment and psychological distress. The overall findings suggested that the urban environment has measurable associations with psychological distress. The evidence supports the need for development of interventions to improve mental health through changing the urban environment. Future work needs to examine the longitudinal effects of the urban environment measured objectively on psychological distress. The impact of the urban environment away from home on psychological distress needs to be further explored.